Gender moderation of intrinsic research productivity antecedents in South African academia. Issue 3 (3rd April 2017) - Callaghan, Chris
Abstract : Purpose: Ascription theory together with human capital theory both predict that, over time, the scarcity of knowledge and skills in increasingly complex working contexts will "crowd out" the influence of arbitrary characteristics such as gender. The purpose of this paper is to test the extent to which job performance determinants of research productivity differ by gender in their contributions to research productivity, in the developing country (South Africa) context, in which gender and other forms of historical discrimination were previously endemic. Design/methodology/approach: Research output was measured as published journal articles indexed by Thomson Reuters Institute for Scientific Information, ProQuest's International Bibliography of the Social Sciences and the South African Department of Higher Education and Training, as well as conference proceedings publications, conference papers presented and published books and book chapters. Structural equation modelling, with critical ratio and χ 2 tests of path moderation were used to test theory predicting gender (sex) differences moderate the potential influence of certain intrinsic determinants of job performance on research productivity, as a form of academic job performance. Findings: Gender is found to moderate the relationship between experience and research productivity, with this relationship stronger for men, who are also found to have higher research output. This is considered a paradox of sorts, as English and African home languages, which proxy racial differences in societal and economic disadvantages and unequal opportunities, are not significantly associated with research output differences. Findings further suggest none of the tested intrinsic effects are moderated by gender, contesting theory from general work contexts. Research limitations/implications: This research applied a cross-sectional design, and did not apply causal methods, instrumental variables or controls for endogeneity. Nevertheless, these are limitations shared with most research in the human resources field, which is constrained by the type of data available in organisational contexts. Further research might do well to investigate non-intrinsic influences on research productivity which may be vulnerable to differences in societal gender roles. Originality/value: This research offers a novel perspective of research productivity and gender inequality in a developing country context of increasing diversity, which might offer useful insights into other contexts facing increasing diversity in higher education. The problem of gender-based inequality in research productivity is empirically identified, and little evidence is found to support the notion that intrinsic effects, including core self-evaluations, are at the heart of this problem. Arguably, these findings reduce the problem space around gender inequality in research productivity, in a context in which other forms of disadvantage might no longer manifest in research productivity inequality.